Is Coagulopathy an Appropriate Therapeutic Target During Critical Illness Such as Trauma or Sepsis?. Issue 2 (August 2017) - Moore, Hunter B.; Winfield, Robert D.; Aibiki, Mayuki; Neal, Matthew D.
Abstract : ABSTRACT: Coagulopathy is a common and vexing clinical problem in critically ill patients. Recently, major advances focused on the treatment of coagulopathy in trauma and sepsis have emerged. However, the targeting of coagulopathy with blood product transfusion and drugs directed at attenuating the physiologic response to these conditions has major potential risk to the patient. Therefore, the identification of coagulopathy as a clinical target is an area of uncertainty and controversy. To analyze the state of the science regarding coagulopathy in critical illness, a symposium addressing the problem was organized at the 39th annual meeting of the Shock Society in the summer of 2016. This manuscript synthesizes the viewpoints of the four expert panelists at the debate and presents an overview of the potential positive and negative consequences of targeting coagulopathy in trauma and sepsis.